The Behavior of a Multi-Story Steel Frame Subject to Measured Fire Using Calibrated Simple Approach - Kim, Robin E.; Piao, Xingyue; An, Jae Hong (Sustainability, 2019)
Structural steels are one of the most popular construction materials with a number of merits, such as cost-effectiveness, durability, lightweight, versatility, etc. However, when exposed to a high temperature, their thermal expansion rate is high and the strength reduces substantially, making the steel structures vulnerable to fire. So far, a number of studies have been performed to understand the behavior of steel in fire. Rigorous tests, from the material to structural level, have led the advancement of modeling techniques. Among various analytical techniques, one of the most widely used approaches is the finite element modeling (FEM). While FEM can demonstrate geometrical and material nonlinearities, due to the complexity, the approach may result in high computational loads to ensure the convergence. Thus, in this paper, a simple calculation method is instead used to understand the steel frame subject to fire, in conjunction with experimentally collected temperature and displacement data. Then, at each temperature (before and after critical temperature and the formation of plastic hinges), the effect of elevated temperature on global behavior is examined using frame analysis. Results of the study have demonstrated that when structural integrity is of concern, the critical temperature of the structure must be examined in terms of fundamental characteristics of the structure.